Efficacy of Rechallenge Chemotherapy in Patients With Sensitive Relapsed Small Cell Lung Cancer. (February 2015) - Wakuda, Kazushige; Kenmotsu, Hirotsugu; Naito, Tateaki; Akamatsu, Hiroaki; Ono, Akira; Shukuya, Takehito; Nakamura, Yukiko; Tsuya, Asuka; Murakami, Haruyasu; Takahashi, Toshiaki; Endo, Masahiro; Nakajima, Takashi; et al.
Abstract : Objectives: To evaluate the efficacy of rechallenge with current induction regimens for sensitive-relapse small cell lung cancer (SCLC) patients. Methods: We defined sensitive relapse as treatment-free interval (TFI≥90 d). Sensitive-relapse SCLC patients who received second-line chemotherapy were separated into those treated with rechallenge chemotherapy (rechallenge group) and those treated with other regimens (other group). The endpoints were overall survival (OS), progression-free survival, and toxicity. Results: Sixty-five patients (19 rechallenge group and 46 other group) were assessable for efficacy and safety evaluation. No significant differences in age, sex, ECOG performance status at relapse, disease extent at diagnosis, or response to first-line treatment were found between the 2 groups, but TFI was significantly longer in the rechallenge group. Twenty-one patients of the other group received amrubicin. There was no significant difference in OS between the 2 groups (median survival time [MST]: rechallenge group, 14.4 mo; other group, 13.1 mo; P =0.51). In the patients treated with amrubicin, MST was 12.6 months. Comparing the rechallenge group with the patients treated with amrubicin, there was also no significant difference in OS ( P =0.38). Both the rechallenge and other group included 11 patients with ex-sensitive relapse (TFI≥180 d). There was no significant difference in OS between the 2 groups (MST 15.7 vs. 26.9 mo, P =0.46). Conclusions: Rechallenge chemotherapy did not prove superior to other chemotherapies, suggesting that monotherapy, such as amrubicin, might be reasonable as second-line chemotherapy for sensitive-relapse SCLC patients.